2007
DOI: 10.1007/s10803-007-0498-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of Home Videotapes to Confirm Parental Reports of Regression in Autism

Abstract: The current study examined consistency between parental reports on early language development and behaviors in non-language domains and observer-coded videotapes of young children with and without autism spectrum disorder (ASD) and autistic regression. Data are reported on 56 children (84% male) with ASD (early onset or autistic regression) and 14 typically developing children (57% male) who had home videotapes. Unique to the current study is the independent identification of loss/no loss for each child by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 42 publications
6
41
0
4
Order By: Relevance
“…Recent papers have pointed out significant complexities in defining and measuring the onset of autism symptoms (18). Studies have demonstrated relatively low correspondence between parent report of onset and home videotape evidence of symptom trajectories (26), with one study showing that 45% of participants clearly demonstrated a regression on videotape that was not reported by parents (27). Similarly, a recent prospective study found that regression was evident in many infants who were developing autism but was reported by only a minority of parents (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers have pointed out significant complexities in defining and measuring the onset of autism symptoms (18). Studies have demonstrated relatively low correspondence between parent report of onset and home videotape evidence of symptom trajectories (26), with one study showing that 45% of participants clearly demonstrated a regression on videotape that was not reported by parents (27). Similarly, a recent prospective study found that regression was evident in many infants who were developing autism but was reported by only a minority of parents (28).…”
Section: Discussionmentioning
confidence: 99%
“…These also are predictive of broader, receptive language problems. Unlike normally-developing children whose word recognition skills begin midway through the first year, children with AD acquire words and word combinations more slowly (Goldberg et al 2008;Landa 2007), and have fewer words or phrases by their first birthday (Mitchell et al 2006). This disparity continues into their second year of life.…”
Section: Prelinguistic Risk Of Language Impairmentmentioning
confidence: 99%
“…Samples of home videos have recently been used to establish the validity of regressive phenomenon in RASD through comparison of videotaped behaviors recorded before and after regression (Goldberg et al 2008;. However, often the recording of these video samples is linked to special family events (e.g., first and second birthdays) that may bookend but be temporally removed from the period of regression.…”
Section: Definitional and Conceptual Problemsmentioning
confidence: 99%
“…In support of the validity of the phenomenon, Rogers (2004) has pointed out that every study that has examined the onset of symptoms in autism has reported a significant minority of children who have exhibited a pattern of developmental regression. Moreover, advances in methods of data collection, such as videotape analysis (Goldberg et al 2008;Maestro et al 2006;, improved interviewing procedures ), more detailed behavioral questionnaires (Goldberg et al 2003;Ozonoff et al 2005), and the use of key historical markers (e.g. birthdays) have helped improve the accuracy of parental reports, and have resulted in better delineation of the existence and the characteristics of regression in ASD.…”
Section: Definitional and Conceptual Problemsmentioning
confidence: 99%